Pengaruh Model Pembelajaran Picture and Picture Terhadap Kemampuan Menulis Puisi Siswa Kelas V Kota Bengkulu - Melsa Fitri; Resnani; Dwi Anggraini (Universitas Bengkulu, 2023)
This research was aimed to analyze the effect of Picture and picture learning model towardstudents' writing poetry skill in 5th class of elementary school in Bengkulu City. This researchwas Quantitative reseacrh. The method used was quasi-experimental and the design wasmatching only posttest control group. The population of this research was 5th class of all elementary school in Bengkulu city whereas the sample was class V of elementary School No 51 was the control class. Both classes used School Based Curriculum (KTSP) and obtain accreditation A. The technique of sampling was stratified sampling. The instrument used wasessay posttest for both control and experimental class. The data of the research was analyzed byusing descriptive analysis, prerequisite test and t test. The result of the research was found that the average score of posttest of the control class was 75,41 and the average score of posttest of the experimental class was 83,18. The result of the t test was found that the t count about 2,02. So, Ha was accepted and Ho was rejected. This result showed that there was the effect of Picture andPicture model learning toward students’ writing poetry skill in 5th Class of elementary school inBengkulu City.